Efeito potencializador do antineoplásico paclitaxel (taxol®) na hiperalgesia inflamatória experimental induzida por zymosan - Cardoso, Mirlane Guimarães de Melo (2003)
Paclitaxel (Taxol®) was the first effective antineoplastic in the management of refractory neoplasias to the conventional chemotherapy. It induces clinically to myelosuppression and sensory peripheral neuropathy boundary and cumulative dose, well documented at literature already. Less often the patients exhibited myalgias and arthralgias. As to concern to the inflammatory pain, there is nothing described do date, aiming to correlate the involvement from pro-inflammatory cytokines with the hyperalgesia genesis associated to PCX since the drug induces the alpha-TNF expression gene. It has already been demonstrated, experimentally by several authors, the essential role of alpha-TNF triggering a set of cytokines which active two components of the inflammatory pain (eicosanoid and sympathetic). Findings of our group showed that zymosan (ZY) administrated intraperitoneal (ip) in mice, induces the release of these cytokines by resident macrophages at the wriggling abdominal model (CA) and that their injection intra-articular rat knees produces a feature periarthritis as a sign of hyperalgesia at articular incapacitation model (IA). Based on these findings, the aim of the present work was to evaluate PCX effect at the modulation of nociceptive response induced by zymosan in two animal models of the inflammatory pain. Then, was injected via ip PCX (8mg/kg/an) before two hours of ZY (1mg/cav;ip) in mice on the CA test. Rats were treated with ip PCX (4,8 mg/kg/an) after one hour ZY intra-articular (250mcg/animal;i-art) for IA test. Both tests, the animals were pre-treated subcutaneous via with COX-1 and COX-2 inhibitors, sympathetic blockade and citokines inhibitors. It was demonstrated that PCX (8mg/kg/an) dose potentiates the inflammatory hyperalgesia at CA model, increasing in 183%, being statistical significant at the level p< 0.001, versus experimental group. Such effect was inhibited at level of significance, p< 0.001 and dependent-dose by indomethacin (ED50 0.05mg/kg), celoxib (ED5013.68mg/kg), atenolol(ED50 0.13mg/kg), talidomide (ED50 23.36mg/kg), penthoxyphylin (ED50 8.40mg/kg) and dexamethasone (ED50 0,71mg/kg). This potential effect of at the IA test was justified at IA model in dose 4mg/kg (p< 0,001) by significant increase of time of suspension the paws through arthritis at third and fourth hours versus experimental group. By same way there was significant inhibition at the level p< 0.001 of this magnification of the pre-treated rats. Latter, PCX (Taxol®) magnified significantly the inflammatory hyperalgesia induced by ZY at CA and IA models, justifying one sided myalgias and artralgias of the patients by using PCX, suggesting the involvement of the hyperalgesic citokines - alpha-TNF, prostanoids and sympathetic mediators of the genesis of this hyper-nociceptive effect.